Back Cover: Control Viscoelasticity of Polymer Networks with Crosslinks of Superposed Fast and Slow Dynamics (Angew. Chem. Int. Ed. 41/2021). Issue 41 (12th July 2021) - Chen, Hao; Zhang, Jin; Yu, Wenting; Cao, Yi; Cao, Zhaozhen; Tan, Yebang
Abstract : A supramolecular crosslink of superposed fast and slow dynamics is reported by Hao Chen, Yi Cao, Yebang Tan et al. in their Research Article on page 22332 . This crosslink exhibits quantitatively tailored molecular dynamics. The well‐defined molecular dynamics of the crosslinks enable precise control over the viscoelasticity and mechanical response of the resulting polymer networks at the molecular level.